Effect of local cold application on glycogen recovery - Tucker, T. J.; Slivka, D. R.; Cuddy, J. S.; Hailes, W. S.; Ruby, B. C (The Journal of Sports Medicine and Physical Fitness, 2012)
The purpose of this study was to investigate the effect of local cold application on muscle glycogen re-synthesis after exercise. Recreationally active male subjects (n=11) completed a 90-minute glycogen depleting ride, followed by 4 h of recovery. During recovery, ice was applied intermittently to one leg (IL) while the subjects other leg (CL) acted as a control. Intramuscular and rectal temperature was recorded continuously. A carbohydrate (1.8 g/kg bodyweight) beverage was supplied at 0 and 2 h post exercise. Muscle biopsies were taken immediately after exercise from the vastus lateralis and at 4 h post exercise for the analysis of muscle glycogen and muscle lactate. Leg circumference was measured 30, 60, 120, 180, and 240 minutes into recovery. The IL was colder than the CL from 15 minutes after initial ice application until the end recovery (P<0.05). Immediate post-exercise glycogen was similar between legs (55.3±7.4 vs. 56.1±7 mmol/kg wet weight for the iced vs. control, respectively). However, muscle glycogen was lower in the IL compared to the CL at 4 h post exercise (72±8.4 vs. 95±8.4 mmol/kg wet weight, respectively; P<0.05). Muscle lactate was lower in the IL after 4 h of recovery compared to the CL (1.6±.2 vs. 2.6±.2 mmol/L, respectively; P<0.05). There was no difference in circumference between IL and CL. These data demonstrate a reduction in muscle glycogen re-synthesis with local cold application.